Primary and recurrent sporadic desmoids: Prognostic factors influencing recurrence-free survival after complete gross resection - Mueller, Christian; Croner, Roland; Klein, Peter; Grützmann, Robert; Vassos, Nikolaos (International Journal of Surgery, 2016)
There is continuing controversy over the significance of prognostic factors in sporadic desmoid-type fibromatosis (DF). Further, only limited data is available in the literature concerning second recurrence in patients with recurrent DF. The purpose of this study was to identify prognostic factors influencing recurrence-free survival (RFS) and to determine rates of local recurrence (LR) in patients with primary and recurrent DF.Fifty-three consecutive patients with DF who underwent surgery at a single institution were identified. As a result of strict exclusion criteria, a homogeneous cohort of thirty-two patients who received macroscopically complete resection was included in this study and split into a primary (PG) and recurrent disease (RG) group. Clinicopathological parameters and immunohistochemical markers were retrospectively and independently analyzed in both groups.The local recurrence rate was 35% for the PG and 33% for the RG. The PG's calculated median time to relapse was 17 months, and the RG's was 29 months. The estimated 1-, 5-, and 8-year RFS rates for the PG were 75%, 64%, and 55% while the corresponding RFS rates for the RG were 69%, 69%, and 52%, respectively. In primary disease, extraabdominal tumor location was the only significant adverse prognostic factor associated with worse RFS (p = 0.008). Whereas in recurrent disease, age >=40 yrs (p = 0.022) and R0 margin status (p = 0.049) correlated with a significantly better outcome.Recurrence in primary and recurrent DF is characterized by different predictive factors and benefits from distinct therapeutic strategies. Immunohistochemical markers are valuable tools in the diagnosis of DF, although have limited potential in predicting the outcome.
EVALuna2:15243